Multi-faceted inhibition of dendritic cell function by CD4+Foxp3+ regulatory T cells. (March 2019) - Seitz, Christina; Liu, Sang; Klocke, Katrin; Joly, Anne-Laure; Czarnewski, Paulo V.; Tibbitt, Christopher A.; Parigi, Sara M.; Westerberg, Lisa S.; Coquet, Jonathan M.; Villablanca, Eduardo J.; Wing, Kajsa; Andersson, John
Abstract: CTLA-4 is required for CD4 + Foxp3 + regulatory T (Treg) cell function, but its mode of action remains incompletely defined. Herein we generated Ctla-4 ex2fl/fl Foxp3-Cre mice with Treg cells exclusively expressing a naturally occurring, ligand-independent isoform of CTLA-4 (liCTLA-4) that cannot interact with the costimulatory molecules CD80 and CD86. The mice did not exhibit any signs of effector T cell activation early in life, however, at 6 months of age they exhibited excessive T cell activation and inflammation in lungs. In contrast, mice with Treg cells completely lacking CTLA-4 developed lymphoproliferative disease characterized by multi-organ inflammation early in life. In vitro, Treg cells exclusively expressing liCTLA-4 inhibited CD80 and CD86 expression on dendritic cells (DC). Conversely, Treg cells required the extra-cellular part of CTLA-4 to up-regulate expression of the co-inhibitory molecule PD-L2 on DCs. Transcriptomic analysis of suppressed DCs revealed that Treg cells induced a specific immunosuppressive program in DCs. Highlights: The cell-extrinsic functions of CTLA-4 are dispensable for regulating CD80/86 expression on DCs. Regulatory T cells use CTLA-4 to induce the co-inhibitory molecule PD-L2 on dendritic cells. Regulatory T cells induce a specific genetic program in suppressed dendritic cells. CTLA-4 is required to restrict the size of the regulatory T cell pool.